2020
DOI: 10.3390/jcm9082339
|View full text |Cite
|
Sign up to set email alerts
|

Hospitalizations for Community-Acquired and Non-Ventilator-Associated Hospital-Acquired Pneumonia in Spain: Influence of the Presence of Bronchiectasis. A Retrospective Database Study

Abstract: To examine and compare in-hospital mortality (IHM) of community-acquired pneumonia (CAP) and non-ventilator hospital-acquired pneumonia (NV-HAP) among patients with or without bronchiectasis (BQ) using propensity score matching. A retrospective observational epidemiological study using the Spanish Hospital Discharge Records, 2016–17. We identified 257,455 admissions with CAP (3.97% with BQ) and 17,069 with NV-HAP (2.07% with BQ). Patients with CAP and BQ had less comorbidity, lower IHM, and a longer mean lengt… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1

Citation Types

0
3
0

Year Published

2021
2021
2023
2023

Publication Types

Select...
6

Relationship

0
6

Authors

Journals

citations
Cited by 6 publications
(3 citation statements)
references
References 51 publications
0
3
0
Order By: Relevance
“…In patients with bronchiectasis, P. aeruginosa is well known to be a common cause of respiratory infection. 23 , 24 Additionally, the presence of P. aeruginosa is associated with more severe disease and a higher risk of mortality. 25 It was previously reported that COPD patients with prior PTB were more likely to have a positive P. aeruginosa culture during an exacerbation, and showed a higher prevalence of bronchiectasis.…”
Section: Discussionmentioning
confidence: 99%
“…In patients with bronchiectasis, P. aeruginosa is well known to be a common cause of respiratory infection. 23 , 24 Additionally, the presence of P. aeruginosa is associated with more severe disease and a higher risk of mortality. 25 It was previously reported that COPD patients with prior PTB were more likely to have a positive P. aeruginosa culture during an exacerbation, and showed a higher prevalence of bronchiectasis.…”
Section: Discussionmentioning
confidence: 99%
“…"Prior pneumonia events" was significantly associated with higher incidence of pneumonia and was robust in these models. This association could be due to unadjusted risk factors of bacterial pneumonia such as neurological disorders associated with dysphagia, chronic lung disease other than COPD like bronchiectasis, diabetes mellitus and malnutrition [25][26][27][28][29].…”
Section: Discussionmentioning
confidence: 99%
“…The Bronchiectasis Severity Index (BSI) scoring system, including physical characteristics, radiological severity, sputum microbiology, dyspnea score, and a history of exacerbation, has been used to predict mortality from bronchiectasis (2). Pneumonia leads to hospitalization and the deterioration of physiological functions in patients with bronchiectasis (8,9). Respiratory failure is the major cause of death in bronchiectasis (10,11).…”
Section: Introductionmentioning
confidence: 99%